Therapeutic delivery of oxygen using artificial oxygen carriers demonstrates the possibility of treating a wide range of diseases - Nijaya Mohanto; Himangsu Mondal; Young-Joon Park; Jun-Pil Jee (Journal of Nanobiotechnology)
Abstract Artificial oxygen carriers have emerged as potential substitutes for red blood cells in situations of major blood loss, including accidents, surgical procedures, trauma, childbirth, stomach ulcers, hemorrhagic shock, and blood vessel ruptures which can lead to sudden reduction in blood volume. The therapeutic delivery of oxygen utilizing artificial oxygen carriers as red blood cell substitutes presents a promising avenue for treating a spectrum of disease models. Apart from that, the recent advancement of artificial oxygen carriers intended to supplant conventional blood transfusions draws significant attention due to the exigencies of warfare and the ongoing challenges posed by the COVID-19 pandemic. However, there is a pressing need to formulate stable, non-toxic, and immunologically inert oxygen carriers. Even though numerous challenges are encountered in the development of artificial oxygen carriers, their applicability extends to various medical treatments, encompassing elective and cardiovascular surgeries, hemorrhagic shock, decompression illness, acute stroke, myocardial infarction, sickle cell crisis, and proficient addressing conditions such as cerebral hypoxia. Therefore, this paper provides an overview of therapeutic oxygen delivery using assorted types of artificial oxygen carriers, including hemoglobin-based, perfluorocarbon-based, stem cell-derived, and oxygen micro/nanobubbles, in the treatment of diverse disease models. Additionally, it discusses the potential side effects and limitations associated with these interventions, while incorporating completed and ongoing research and recent clinical developments. Finally, the prospective solutions and general demands of the perfect artificial oxygen carriers were anticipated to be a reference for subsequent research endeavors. Graphical Abstract